Development of a cadaveric head and neck cancer model and three-dimensional analysis of margins in surgical navigation-aided ablations. Issue 6 (June 2022) - Ferrari, Marco; Taboni, Stefano; Carobbio, Andrea L.C.; Buffoli, Barbara; Rampinelli, Vittorio; Mattavelli, Davide; Schreiber, Alberto; Verzeletti, Vincenzo; Ravanelli, Marco; Daly, Michael J.; Chan, Harley H.L.; Sahovaler, Axel; et al.
Abstract: Introduction: The adequacy of the surgical resection is the main controllable variable that is in the hands of the surgical team. There exists an unmet need to increase the rate of negative margins, particularly in cancers invading the craniofacial area. The study aimed 1) at developing a gross tumor model to be utilized for research, educational, and training purposes and 2) establishing the 3-dimensional relationship between the outer surface of the surgical specimen and tumor surface and test the effect of guiding ablations on cadavers with surgical navigation (SN). Material and methods: Seven cadaver heads were employed to create 24 craniofacial tumor models. Simulation of tumor resections was performed by 8 surgeons. Fourteen and 10 resections were performed with and without SN-guidance, respectively. Gross specimens underwent computed tomography and 3-dimensional analysis through dedicated software. Task load was assessed through a validated questionnaire. Tumor model reliability was studied based on visual analogue scale rate by surgeons and radiologists. Results: SN reduced the rate of margin involvement, particularly by decreasing the percentage of the gross specimen outer surface involvement in areas uncovered by normal bony structures. The workload of SN-aided ablations was found to be medium-to-somewhat-high. Tumor model reliability was deemed satisfactory except for the extension to bony structures. Conclusions: A gross tumor model for head and neck cancers involving the craniofacial area was developed and resulted satisfactorily reliable from both a surgical and radiologic standpoint. SN reduced the rate of margin involvement, particularly by improving delineation of bone-uncovered areas.